Productivity at site level in the construction industry : an overview of factors that influence productivity and a proposed method to measure, monitor & improve productivity - Fourie, L.(Louis) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1989.